Safe Blood to Save Life: A Study to Assess the Knowledge, Attitude, and Practice Regarding Blood Donation among Undergraduate Medical Students (Medical Forum Monthly, 2021)
Objective: To explore the Knowledge, Attitude and Practice regarding blood donation among undergraduate medical students in Rashid Latif Medical College, Lahore.Study Design: Descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at the Rashid Latif Medical College, Lahore from July to September 2019.Materials and Methods: A total of 347 students who were present on the day of the survey and expressed their consent for participation were enrolled in the study. A structured validated questionnaire was used as a study tool.Results: A total of 347 undergraduate medical students responded to the questionnaire, 191 were in Group A and 156 were in Group B. In group A 29 (15%) donated blood, while in group B donors are only 5%. Majority of the students in both groups know their blood groups. Knowledge about the blood donations among medical students is inadequate.Conclusion: Inadequate knowledge indicates a need to incorporate topics of transfusion medicine in undergraduate curricula. Opportunities for blood donations should be created regularly to increase the sense of social responsibility among medical students.